The Use of Cash Waqf Funds and Its Various Legal Problems in Indonesia - Faisal Faisal (International Journal Reglement & Society (IJRS), 2021)
Cash waqf is waqf carried out by a person, group of people, and institutions or legal entities in the form of cash. In the fiqh literature it is stated that the Hanafi school has practiced this waqf in society. In Islamic society in general cash waqf has long been practiced, but the contract still mentions land waqf. For example, the construction of a mosque requires a plot of land with an area of 500 square meters, with a price of 50,000,000; then the land is divided into 500 lots. Thus, obtained the price of 100 per meter. Furthermore, it is marketed to the wider community for land waqf by way of per meter with an affordable value, and the wakif pays according to the number of meters he wants to waqf. Today, by looking at the times, and something that cannot be avoided anymore about the importance of money (in the form of cash) in transactions, the Indonesian ulema. The procedure used to collect data in this study is in the form of documentation, namely the guidelines used in the form of notes or quotes, searching for legal literature, books and others related to the identification of problems in this study both offline and online. Analysis of legal materials is carried out using the content analysis method (centent analysis method) which is carried out by describing the material of legal events or legal products in detail in order to facilitate interpretation in the discussion. According to Law no. 41 of 2004 concerning waqf and Government Regulation no. 42 of 2006 can be summarized several waqf concepts as follows. Waqf is a legal act of wakif to separate and/or surrender part of his property to be used forever or for a certain period of time in accordance with his interests for the purposes of worship and/or general welfare according to sharia. Waqf is carried out by fulfilling the elements of waqf. In the management of waqf, there are still various kinds of problems that lead to civil matters. Regarding civil issues, the relationship between humans and humans in daily practice can often lead to legal relationships, which in that relationship between one another will give rise to rights and obligations that must be fulfilled by the parties so that in legal terms it is known as material civil law. and formal civil law.